Politicians' coherence and government debt - Giorgio Bellettini; Paolo Roberti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2016)
We model a society that values the coherence between past policy platforms and current implemented policy, and where policy platforms partially commit candidates to their future actions. If an incumbent politician seeks to be reelected, she has to use her platforms to commit to moderate policies that can be distant from her most preferred one. Commitment is related to the incoherence cost that politicians pay when they renege on promised platforms. In this context, we suggest a novel mechanism through which issuing government debt can affect electoral results. Debt is exploited by an incumbent politician, who is in favor of low spending, to damage the credibility of her opponent's policy platforms, and be reelected. A higher level of debt decreases voters' most preferred level of spending, and makes the opponent's past platform a losing policy. Even if the latter chose to update her proposal, she would not be able to credibly commit to it, given the incoherence cost associated to changing proposals.
Keywords: D72; H63; D78; 330